Admission to the Regular Ward is Safe Following Uncomplicated Craniosynostosis Surgery: A Retrospective Study. (September 2021) - Sileo, Deseray; Walch, Frank; French, Brooke M.; Greenan, Krista; Graber, Sarah; Andrews, Maureen; Alexander, Allyson; Nguyen, Thanh; Mason, Aaron; Winston, Ken R.; Wilkinson, C Corbett
Background: At our craniofacial center patients are routinely admitted to a regular ward, or floor, rather an intensive care unit (ICU) after uncomplicated craniosynostosis surgery. In this study, we review the safety of our postoperative placement policy, examining the rate of transfer from floor to ICU.Methods: The charts of patients who underwent craniosynostosis surgery from 2009 through 2017 at a single children's hospital were reviewed. Postoperative hospital courses were characterized as preoperatively-planned ICU admission, perioperatively-planned ICU admission, or primary floor admission. The primary outcome was transfer from floor to ICU. Secondary outcomes included duration of hospitalization.Results: Chart review yielded 420 patients. Three hundred sixty-eight (88%) were admitted directly to the floor and 52 (12.0%) directly to an ICU. Of patients admitted to the floor, 2 (0.5%) were transferred to an ICU. Twenty-four patients with syndromic and 20 patients with multisutural craniosynostosis were admitted to the floor. Only 1 patient from each group (the same patient; 4.2% and 5.0%, respectively), was transferred to an ICU. Thirty-two ICU admissions were preoperatively planned and 20 were perioperatively planned. Reasons for preoperatively planned ICU admission included significant comorbidities and type of surgery. Reasons for perioperatively planned ICU admissions included significant intraoperative adverse events, excessive blood loss, and failure of clearance from the post-anesthesia care unit (PACU). Patients admitted to the ICU had a statistically significant longer mean length of hospitalization (4.8 days vs 2.7 days) than did patients admitted to the floor.Conclusions: Most postoperative craniosynostosis surgery patients—including patients with syndromic and/or multisutural synostosis—are managed safely on the floor at our center. Some patients still need postoperative ICU admission, but are easily identified preoperatively, intraoperatively, or in the PACU. Our findings should be applicable to other large craniofacial centers.